2019
DOI: 10.1111/zph.12628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterization of Giardia spp. and Cryptosporidium spp. in dogs in Iqaluit, Nunavut, Canada

Abstract: There are few epidemiologic studies on the role of dogs in zoonotic parasitic transmission in the Circumpolar North. The objectives of this study were to: (a) estimate the faecal prevalence of Giardia spp. and Cryptosporidium spp. in dogs; (b) investigate potential associations between the type of dog population and the faecal presence of Giardia spp. and Cryptosporidium spp.; and (c) describe the molecular characteristics of Giardia spp. and Cryptosporidium spp. in dogs in Iqaluit, Nunavut. We conducted two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…The assemblages A and B are further divided into sub-genotypes AI, AII, AIII, BIII and BIV. Typical genotypes in dogs are C and D, but A and B can also be found, and exceptionally even E and F ones [ 6 , 9 , 12 , 14 , 20 ]. Genotype F is common in cats, which can be infected also by genotype A, E and rarely C [ 6 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assemblages A and B are further divided into sub-genotypes AI, AII, AIII, BIII and BIV. Typical genotypes in dogs are C and D, but A and B can also be found, and exceptionally even E and F ones [ 6 , 9 , 12 , 14 , 20 ]. Genotype F is common in cats, which can be infected also by genotype A, E and rarely C [ 6 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The varying prevalence values may reflect variable living conditions (e.g. kennel, breeder or private dogs) (Giangaspero et al 2006 ; Hamnes et al 2007 ; Palmer et al 2008 ; Gil et al 2017 ; Sauda et al 2018 ; Alves et al 2018 ; Itoh et al 2019 ; Julien et al 2019 ), but different sampling strategies and laboratory methods may contribute to this striking variation. In China and Brazil, prevalence was 6.9% and 10.4%, respectively, irrespective of keeping conditions (Li et al 2019 ; Homem et al 2019 ) which is quite close to the values found for Eastern Germany in the present study which may indicate that regional differences are not of great impact.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the genus Cryptosporidium includes 45 different species (Khan et al 2018;Ježková et al 2021). Although infection in dogs has been associated mostly with Cryptosporidium canis (Uehlinger et al 2013;Gil et al 2017;Itoh et al 2019;Julien et al 2019), the zoonotic species Cryptosporidium parvum has been detected also (Giangaspero et al 2006;Sotiriadou et al 2013;Alves et al 2018). In addition, other species like C. muris and C. meleagridis have been found occasionally (Hajdušek et al 2004;Lupo et al 2008;Ryan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to determine whether T. gondii is present in clams harvested for food in Iqaluit, Nunavut. The clams for this study were collected via a community‐based approach as part of a project investigating enteric illness in Iqaluit (Julien et al., 2019; Manore et al., 2020; Masina et al., 2019).…”
Section: Introductionmentioning
confidence: 99%